Study of semi-transparent conductive layers for the realization of high quantum efficiency transmission mode CsI photocathodes for vacuum photodetectors. (18th July 2017) - Barbato, F.C.T.; Valentini, A.; Casamassima, G.; Campajola, L.; Capua, F. Di
Abstract: We worked on the R&D of an innovative photodetector, the Vacuum Silicon Photomultiplier Tube (VSiPMT). The VSiPMT is composed by a photocathode and a solid state amplification stage. A semi-transparent conductive layer is necessary to supply voltage and to obtain a highly efficient CsI photocathode. Since the literature is poor on this topic we performed a systematic and detailed study of a set of semi-transparent conductive layers, made by different material and thickness. A CsI photocathode was evaporated on each sample. The impact of the semi-transparent conductive layer on the quantum efficiency of the photocathode is discussed.